Pulsed-wave laser additive manufacturing of CrCoNi medium-entropy alloys with high strength and ductility - Gao, Shubo (2025)
One of the most popular medium- and high-entropy alloys is CrCoNi alloy, renowned for its outstanding mechanical properties, particularly at cryogenic temperatures. However, further enhancing the yield strength of CrCoNi at room temperature while maintaining its high ductility remains challenging. In this study, we explore the potential of using a pulsed-wave laser in the powder bed fusion, a dominant metal additive manufacturing (AM) technique, to achieve exceptional room-temperature strength–ductility synergy in CrCoNi alloy. The pulsed-wave laser induces extra thermal cycles, generating additional pre-existing dislocations that are uniformly distributed within the interiors of solidification cells, a phenomenon distinct from conventional AM. These pre-existing dislocations not only enhance the room-temperature yield strength exceeding 800 MPa but also trigger the onset of deformation twinning prior to 2% strain. This early activation of deformation twinning contributes to steady work hardening throughout the entire plastic deformation, resulting in a large uniform elongation of nearly 40%. Our work offers valuable insights for designing novel AM processes with pulsed-wave lasers to advance the fabrication of high-value and high-performance alloys.